2023
DOI: 10.1080/22221751.2023.2249121
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization against Omicron subvariants after BA.5/BF.7 breakthrough infection weakened as virus evolution and aging despite repeated prototype-based vaccination 1

Hongyu Wang,
Quanlin Xue,
Haocheng Zhang
et al.

Abstract: Background: Omicron had swept the mainland China between December 2022 and January 2023, while SARS-CoV-2 still continued to evolve. To fully prepare for the next wave, it’s urgent to evaluate the humoral immune response post BA.5/BF.7 breakthrough infection against predominant sub-lineages among existing vaccination strategies and the elders. Method: This study enrolled a longitudinal young-adult cohort from 2/3-dose vaccination to 1 month after breakthrough infection, and an elder cohort at 1 month after bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…What's more, due to relatively poor immunogenicity, 44,45 the immune imprinting induced by WT inactivated vaccines may be weaker than others after Omicron subvariants reinfection, which can explain the higher NAbs against Omicron subvariants in homologous vaccinated group. Different from the documented study, 30 we find that the age has a slight effect on antibody response after Omicron BA.5 BTI and shows no influence on antibody response after XBB reinfection, revealing that muti‐antigen exposure may gradually alleviate the difference between ages. Also, we confirmed the result that elderly people with comorbidities of hypertension and cerebral apoplexy had lower antibody responses than others 46,47 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…What's more, due to relatively poor immunogenicity, 44,45 the immune imprinting induced by WT inactivated vaccines may be weaker than others after Omicron subvariants reinfection, which can explain the higher NAbs against Omicron subvariants in homologous vaccinated group. Different from the documented study, 30 we find that the age has a slight effect on antibody response after Omicron BA.5 BTI and shows no influence on antibody response after XBB reinfection, revealing that muti‐antigen exposure may gradually alleviate the difference between ages. Also, we confirmed the result that elderly people with comorbidities of hypertension and cerebral apoplexy had lower antibody responses than others 46,47 .…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with the previous studies, 30,38–40 our findings confirm that the NAb titers against Omicron XBB.1.5 and BA.2.86 that elicited by Omicron BA.5 BTI are remained at low levels and are not able to provide enough protection against subsequent Omicron XBB reinfection. Importantly, our results and others both demonstrate that Omicron XBB reinfection enhances the neutralizing ability against all measured Omicron subvariants, 6,32 revealing that Omicron subvariants reinfection may alleviate WT vaccination‐induced immune imprinting and generate broad neutralization responses 41 .…”
Section: Discussionsupporting
confidence: 92%
“… 26 However, a recent study showed that repeated prototype-based booster vaccines did not improve neutralizing antibodies against Omicron subvariants. 27 In contrast, our study provided solid evidence that the RBD from WT SARS-CoV-2 does contain some conserved epitopes recognized by antibodies such as SA55 and BN03, despite the acceleration of mutations in JN.1, BA.2.86, and XBB subvariants. Even with immune pressure, BA.2.86/JN.1 with over 30 mutations still did not change the conserved epitopes for the bnAbs such as SA55 and BN03, implying that the evolution of SARS-CoV-2 might not break through the completely conserved and unmutated epitopes, thus providing proof of concept for the strategy of “non-changeable against changeable” to develop universal COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 59%
“…Research on omicron shows that, in addition to producing antibodies against vaccine strains, immunization with inactivated vaccines also produced neutralizing antibodies against D614G and delta mutant strains in most HIV-infected individuals, but the neutralizing antibody levels were significantly lower than those in the general population ( 43 ). Wang et al ( 44 ) studied the humoral responses of individuals of different ages receiving different vaccination strategies infected with omicron BA.5/BF.7 before and after breakthrough infection in China from December 2022 to January 2023. They found that the newer variants showed increased immune evasion, and the effectiveness of prototype-based booster vaccine schemes on emerging variants such as CH.1.1 and XBB.1.5 continued to weaken.…”
Section: The Clinical Characteristics and Prognosis Of People Living ...mentioning
confidence: 99%
“…They found that the newer variants showed increased immune evasion, and the effectiveness of prototype-based booster vaccine schemes on emerging variants such as CH.1.1 and XBB.1.5 continued to weaken. Repeated prototype-based booster vaccines may therefore not further enhance neutralizing antibodies against new mutations ( 44 ). Low levels of neutralizing antibodies are an important reason for SARS CoV-2 breakthrough infection ( 45 ), suggesting that antibody responses must be monitored in PLWH after COVID-19 vaccination.…”
Section: The Clinical Characteristics and Prognosis Of People Living ...mentioning
confidence: 99%